ANALYSIS OF ATMOSPHERIC DYNAMICS DURING TAILWIND PHENOMENA ON THE RUNWAY OF KUALANAMU AIRPORT - Tambunan, Nensy Nindy; Frida, Erna; Darmawan, Yahya (Universitas Mataram, 2023)
A tailwind, a wind component in aviation, can pose risks during aircraft takeoff and landing by blowing from the aircraft's rear. At Kualanamu Airport on August 02, 2022, Air Navigation Indonesia (AirNav) reported an incident where an aircraft had to abort landing due to a tailwind on the runway. This study analyzes the atmospheric dynamics contributing to tailwind disruptions on that specific day. The analysis involved various steps, including assessing upper-level air humidity using reanalysis data processed with the GrADS application, evaluating air instability through the computation of TT, KI, and SI indexes using the RaOB application, and examining cloud formation using Himawari-9 EH satellite imagery. The analysis revealed the presence of Cumulonimbus clouds around Deli Serdang Regency on August 02, 2022, which led to tailwind effects at Kualanamu Airport. Cumulonimbus clouds are often associated with unstable atmospheric conditions and can generate severe weather events like thunderstorms, heavy rainfall, and strong winds. Cumulonimbus clouds indicate the likelihood of convective activity and strong winds. The strong winds caused by these clouds probably disrupted the Tailwind on the runway at Kualanamu Airport.